Loss of Functional Endothelial Connexin40 Results in Exercise-Induced Hypertension in Mice. Issue 3 (March 2015) - Morton, Susan K.; Chaston, Daniel J.; Howitt, Lauren; Heisler, Jillian; Nicholson, Bruce J.; Fairweather, Stephen; Bröer, Stefan; Ashton, Anthony W.; Matthaei, Klaus I.; Hill, Caryl E.
Abstract : During activity, coordinated vasodilation of microcirculatory networks with upstream supply vessels increases blood flow to skeletal and cardiac muscles and reduces peripheral resistance. Endothelial dysfunction in humans attenuates activity-dependent vasodilation, resulting in exercise-induced hypertension in otherwise normotensive individuals. Underpinning activity-dependent hyperemia is an ascending vasodilation in which the endothelial gap junction protein, connexin (Cx)40, plays an essential role. Because exercise-induced hypertension is proposed as a forerunner to clinical hypertension, we hypothesized that endothelial disruption of Cx40 function in mice may create an animal model of this condition. To this end, we created mice in which a mutant Cx40T152A was expressed alongside wildtype Cx40 selectively in the endothelium. Expression of the Cx40T152A transgene in Xenopus oocytes and mouse coronary endothelial cells in vitro impaired both electric and chemical conductance and acted as a dominant-negative against wildtype Cx40, Cx43, and Cx45, but not Cx37. Endothelial expression of Cx40T152A in Cx40T152ATg mice attenuated ascending vasodilation, without effect on radial coupling through myoendothelial gap junctions. Using radiotelemetry, Cx40T152ATg mice showed an activity-dependent increase in blood pressure, which was significantly greater than in wildtype mice, but significantly less than in chronically hypertensive, Cx40knockout mice. The increase in heart rate with activity was also greater than in wildtype or Cx40knockout mice. We conclude that the endothelial Cx40T152A mutation attenuates activity-dependent vasodilation, producing a model of exercise-induced hypertension. These data highlight the importance of endothelial coupling through Cx40 in regulating blood pressure during activity. Abstract : Supplemental Digital Content is available in the text.